Finite element modelling for free vibration response of cracked stiffened FGM plates - Thom, Do Van; Duc, Doan Hong; Minh, Phung Van; Tung, Nguyen Son (Vietnam Journal of Science and Technology, 2020)
This paper presents the new numerical results of vibration response analysis of cracked FGM plate based on phase-field theory and finite element method. Effects of geometrical and material properties on the vibration behaviors of the plate are investigated in this work. The computed results show that the crack and stiffener have a strong influence on both the vibration responses and vibration mode shapes of the structure. The computed results can be used as a good reference to study some related mechanical problems